2014
DOI: 10.1159/000362379
|View full text |Cite
|
Sign up to set email alerts
|

Fine Needle Aspiration Cytology of Acinar Cell Cystadenoma of the Pancreas

Abstract: Background: Acinar cell cystadenoma (ACC) is a recently recognized cystic lesion of the pancreas that demonstrates acinar differentiation and is currently believed to behave in a benign fashion. ACC enters the differential diagnosis of pancreatic cystic lesions alongside better recognized entities such as mucinous cystic and intraductal papillary mucinous neoplasms. Although uncommon, patients with ACC can undergo fine needle aspiration (FNA) of the lesion. However, the diagnosis is rarely made on cytologic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…The presence of inspissated material in pancreatic cysts seen on cytology specimens has only been rarely reported previously as case reports . Yergiyev et al showed the cytologic features of an acinar cell carcinoma that contained inspissated material with images showing similar cytomorphology to the inspissated fan‐like material seen in many of the cases described herein . Similar to one lymphoepithelial cyst with inspissated cyst material in this report, VandenBussche and Maleki have also described inspissated cyst material in squamous‐lined cysts of the pancreas, material that resembled Curschmann spirals in their series .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The presence of inspissated material in pancreatic cysts seen on cytology specimens has only been rarely reported previously as case reports . Yergiyev et al showed the cytologic features of an acinar cell carcinoma that contained inspissated material with images showing similar cytomorphology to the inspissated fan‐like material seen in many of the cases described herein . Similar to one lymphoepithelial cyst with inspissated cyst material in this report, VandenBussche and Maleki have also described inspissated cyst material in squamous‐lined cysts of the pancreas, material that resembled Curschmann spirals in their series .…”
Section: Discussionsupporting
confidence: 78%
“…The presence of inspissated material in pancreatic cysts seen on cytology specimens has only been rarely reported previously as case reports . Yergiyev et al showed the cytologic features of an acinar cell carcinoma that contained inspissated material with images showing similar cytomorphology to the inspissated fan‐like material seen in many of the cases described herein .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Retrospective reviews 12,16,17 of fourteen cases of FNAB-obtained cyst fluids from resection-diagnosed acinar cell cystadenomas report six non-diagnostic cases, 12,16 four negative/benign cases, 12,16 one suggestive of a neuroendocrine neoplasm, 12 one interpreted as a cystic mucinous neoplasm, 17 and one deemed suspicious for adenocarcinoma. Retrospective reviews 12,16,17 of fourteen cases of FNAB-obtained cyst fluids from resection-diagnosed acinar cell cystadenomas report six non-diagnostic cases, 12,16 four negative/benign cases, 12,16 one suggestive of a neuroendocrine neoplasm, 12 one interpreted as a cystic mucinous neoplasm, 17 and one deemed suspicious for adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective reviews 12,16,17 of fourteen cases of FNAB-obtained cyst fluids from resection-diagnosed acinar cell cystadenomas report six non-diagnostic cases, 12,16 four negative/benign cases, 12,16 one suggestive of a neuroendocrine neoplasm, 12 one interpreted as a cystic mucinous neoplasm, 17 and one deemed suspicious for adenocarcinoma. 17 In our case, the diagnosis of a cyst with high-grade epithelial atypia was initially made due to the striking hypercellularity of the sample being composed of small cells with increased nuclear to cytoplasmic ratio and focally coarse chromatin. Retrospective staining of the cell block with periodic acid Schiff with diastase digestion (PAS-D) highlighted apical PAS-D1 granules in these cells.…”
Section: Discussionmentioning
confidence: 99%